Integrating Community Service with International Internship Programs: Introducing Pancasila Values at Sanggar Belajar Sri Muda and Kuala Langat, Malaysia - Khusnul Khatimah; Farhan Yulistiyawan; Rosinta; Shofia Alya Dzakiriah; Panesa Kartini (Journal of Empowerment and Community Service (JECSR), 2023)
This paper examines the integration of community service through an International Internship Program (KKN Internasional) at Universitas Muhammadiyah, aimed at introducing and teaching the values of Pancasila to Indonesian migrant children at Sanggar Belajar Sri Muda and Sanggar Belajar Kuala Langat in Malaysia. The study assesses the program's goals, methodologies, challenges, and the impact of the intervention on both the students and the community. Through participatory teaching methods and cultural exchange, the project highlights the importance of character education and intercultural communication in international service learning. Despite challenges such as resource limitations and cultural differences, the program successfully contributed to the community and enriched the participants' educational and personal growth. The findings suggest that such international community service programs play a vital role in fostering cross-cultural understanding and promoting national identity abroad.